DETERMINATION OF SPECIFIC HEAT CAPACITIES OF LIQUIDS FROM SOME CONSUMABLE ITEMS - Joseph Gordian Atat , Joseph Gordian Atat; Bassey Umoren, Emmanuel; Samuel Ekpo , Sunday; Akpan Umoette, Unyime (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
This study was done to obtain the Specific Heat Capacities (SHC) of some liquids from some intake items (they are consumed widely in Niger Delta, Nigeria). These items are vegetables (Afang leaf, Pumpkin leaf, Bitter leaf, Scent leaf, Water leaf), fruits (Orange, Cucumber, Pineapple, Watermelon, Lime) and juice (Ribena, Chivita Exotic, Chivita Happy Hour, Chivita Active and Five Alive). Calorimeter was used and Method of mixtures was adopted for this finding. Measured parameters were obtained in the laboratory. Microsoft Excel was used for other analyses and computation of results.